A Forgotten Book by a Marginalised Anthropologist. (September 2019) - Guha, Abhijit
The idea of conducting an anthropological survey on the famine-affected people in Bengal in 1943 was planned and executed by a low profile teacher named Tarak Chandra Das. T.C. Das was not a member of any political party nor did he run any NGO. Indeed, he is a forgotten personality in the annals of Indian anthropology despite his original and groundbreaking contributions to social anthropology and sociology. Historiographers and encyclopaedia writers of Indian anthropology have simply forgotten the name of this legendary anthropologist. This paper is an attempt to remind scholars of how T.C. Das' collection of data based on rigorous fieldwork and observation formed the backbone of his exceptional book, Bengal Famine.